CLIMATE CHANGE AWARENESS AND CLIMATE ANXIETY AMONG ADOLESCENTS IN DENPASAR: A CROSS-SECTIONAL STUDY - Kadek Dewi Cahyani; Indah Permata Sari; Sigit Mulyono (Universitas Airlangga, 2026)
Introduction: Climate change anxiety represents a frequently overlooked yet significant issue with profound implications for adolescent development. While environmental awareness among youth serves as a crucial foundation for pro-environmental behaviors, research examining the relationship between climate change awareness and anxiety levels among adolescents in Denpasar City remains limited. This study aimed to assess whether adolescents' climate change awareness predicts climate anxiety levels. Method: A cross-sectional study was conducted with 434 high school students in Denpasar using online surveys (February-April 2025) using three validated instruments: a demographic questionnaire, a climate change awareness scale adapted from United Nations Development Programme (UNDP) materials and integrated with Indonesian educational standards, and the Climate Change Anxiety Scale Short Form (CCAS-S Instrument reliability testing ).yielded Cronbach's alpha values of 0.60 for the awareness scale and 0.90 for the CCAS-S. Statistical analysis using descriptive methods and the Chi-square test revealed a significant positive correlation between climate change awareness and anxiety levels (p<0.05). Result: The heightened climate change awareness may potentially increase anxiety among adolescents. Conclusion: Developing comprehensive school health-based interactive education promotion programs emphasizing climate adaptation and mitigation strategies through multisectoral collaboration. Keywords: adolescents health; awareness; climate change; climate anxiety.